Decomposing discrimination: Why a holistic approach to racism hides more than it reveals - Ruud Koopmans (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
In recent debates on "race" and "racism", a broad definition has emerged that encompasses phenotypic appearance as well as ethnicity and religion. In addition, the "intersectional" interactions between these different characteristics are a core element of this holistic concept of racism. On the basis of labor market and survey experiments, this article shows that such a concept of racism is not very helpful in understanding actual patterns of discrimination. Phenotype, ethnicity and religion each have independent effects on discrimination. Tendencies towards discrimination differ greatly between social and political groups and are not limited to the majority population. – – In jüngeren Diskussionen zu "Rasse" und "Rassismus" hat sich eine breite Definition durchgesetzt, die sowohl phänotypisches Aussehen als auch Ethnizität und Religion umfasst. Außerdem werden in dieser ganzheitlichen Rassismuskonzeption die "intersektionellen" Wechselwirkungen zwischen diesen verschiedenen Merkmalen betont. Auf der Grundlage eines Arbeitsmarktexperiments sowie eines Umfrageexperiments zeigt dieser Beitrag, dass ein solcher Rassismusbegriff wenig hilfreich ist, um tatsächliche Diskriminierungsmuster zu verstehen. Phänotyp, Ethnizität und Religion üben jeweils voneinander unabhängige Effekte auf Diskriminierung aus. Diskriminierungstendenzen unterscheiden sich stark zwischen sozialen und politischen Gruppen und sind nicht auf die Mehrheitsbevölkerung begrenzt.
Keywords: J15; C93; J61; 300; Rassismus; Diskriminierung; Intersektionalismus; Ethnizität; Religion; Racism; discrimination; intersectionalism; ethnicity; religion